Laccase-catalysed depolymerisation of lignin model oligomers - Woodward, Alison Francesca (2017)
Laccase-catalysed depolymerisation of lignin offers substantial opportunities to form bio-derived aromatic chemicals. Laccase works with exquisite selectivity to oxidise the 5-5’ and β-5’ linkages in lignin and to cleave the β-O-4’ linkages in the presence of 1-hydroxybenzotriazole (1-HBT). However, the laccase/1-HBT system is inefficient when applied to industrial lignin, and the complexity of the product mixtures hinders rapid optimisation. Therefore, I studied laccase-catalysed oxidation of three synthetic lignin model oligomers, which had well-defined structures, yielded analytically tractable product mixtures, and, thus, permitted faster optimisation. Solvent systems were developed to dissolve the lignin model oligomers and retain laccase activity, which aided mass transfer. Models of “hardwood” (S:G 1:1) and “softwood” (G only) lignin containing nonphenolic β-O-4’ linkages (Angewandte Chemie-International Edition, 54, 258) were oxidised quickly by benzylic carbonyl formation (>60% in 24 h), or β-O-4’ bond cleavage. Approximately 25% of the linkages in the “hardwood” (S:G 1:1) oligomer were cleaved in 24 h. A more complex model of “softwood” lignin, containing β-5’, β-O-4’ and 5-5’ phenolic linkages (Green Chemistry, 15, 3031), was oxidised just as rapidly, but reaction products in this case were phenolic dimers that repolymerised. Therefore, I conclude that future bio-production of aromatic chemicals from lignin will depend on the development of improved lignin extraction procedures to allow retention of the β-O-4’ linkages, which will produce more efficient enzymatic depolymerisation.